2022
DOI: 10.1200/op.22.00051
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Lowest-Cost Pharmacy for Cancer Supportive Care Medications: Not So Easy

Abstract: PURPOSE: To decrease the financial burden on people with cancer, clinicians and patients increasingly use medication price comparison websites to seek pharmacies where medications may be cheaper. Shopping around at different pharmacies can add additional time and logistic burden to patients and care partners. We sought to determine whether a single pharmacy consistently offered the lowest price for symptom control medications. METHODS: We compiled medications/formulations used to manage two common cancer-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We also did not include the time spent in other home-based care, such as telephone visits, virtual appointments, or of activities, such as picking up medications at private pharmacies, not captured in the electronic medical record. 16,17 The primary source of contact days was frequent outpatient visits-these may in fact be more burdensome to patients and care partners since they impose daily travel and logistic burdens, in addition to psychological reminders to patients about their sickness. 18,19 The median survival of the cohort, approximately 6 months, is similar to the other real-world studies and lower than what is reported in contemporary clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not include the time spent in other home-based care, such as telephone visits, virtual appointments, or of activities, such as picking up medications at private pharmacies, not captured in the electronic medical record. 16,17 The primary source of contact days was frequent outpatient visits-these may in fact be more burdensome to patients and care partners since they impose daily travel and logistic burdens, in addition to psychological reminders to patients about their sickness. 18,19 The median survival of the cohort, approximately 6 months, is similar to the other real-world studies and lower than what is reported in contemporary clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that it is beneficial for patients to comparison price shop. In an analysis of medications prescribed for nausea/vomiting and cachexia/anorexia associated with cancer, Etteldorf et al 22 evaluated prices using GoodRx discount cards at 9 Minneapolis retail pharmacies and found that no single pharmacy consistently offered the lowest price across different formulations. Hauptman et al 9 previously established that, in the absence of discount cards, generic drugs for HF show wide variability in pricing among retail pharmacies in a 2-state Midwest region.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most of these programs solve problems for uninsured patients but create complications for insured patients with high out-of-pocket costs who try to balance the best ways to obtain medications and may end up creating even more piecemeal ways for how they obtain care. 10 Further, many, if not all of these coupon programs still cannot be used at the same time as insurance, so even if patients are able to receive a lower-priced medication through the program, it would not contribute to their annual insurance deductible.…”
mentioning
confidence: 99%